Enhanced Potassium Ion Battery by Inducing Interlayer Anionic Ligands in MoS1.5Se0.5 Nanosheets with Exploration of the Mechanism. Issue 21 (20th April 2020) - Fan, Hai‐Ning; Wang, Xing‐Yong; Yu, Hai‐Bo; Gu, Qin‐Fen; Chen, Shan‐Liang; Liu, Zheng; Chen, Xiao‐Hua; Luo, Wen‐Bin; Liu, Hua‐Kun
Abstract: The strategy of inducing interlayer anionic ligands in 2D MoS1.5 Se0.5 nanosheets is employed to consolidate the interlayer band gap and optimize the electronic structure for the potassium ion battery. It combines complementary advantages from two kinds of anionic ligands with high conductivity and good affinity with potassium ions. The potassium ion diffusion rate is accelerated as well by an optimized lower energy barrier for ion diffusion pathways, with the formation of highly reversible KMo3 Se3 crystal other than K0.4 MoS2 /K2 MoS4, which encounters a much slower electro/ion diffusion rate upon discharging. These advances deliver enhanced potassium storage properties with excellent cycling stability, with retained specific capacity of 531.6 mAh g −1 at a current density of 200 mA g −1 even after 1000 cycles, and high rate capability with specific capacity of 270.1 mAh g −1 at 5 A g −1 . The insertion and conversion mechanism are also elucidated by a combination of density functional theory computations and in situ synchrotron measurements. Abstract : The strategy of inducing interlayer anionic ligands in 2D MoS1.5 Se0.5 nanosheets is employed to consolidate the interlayer band gap and optimize the electronic structure for the potassium ion battery. It combines complementary advantages from two kinds of anionic ligands with high conductivity and good affinity with potassium ions.